Chronic stress dysregulates amygdalar output to the prefrontal cortex. (1st September 2018) - Lowery-Gionta, Emily G.; Crowley, Nicole A.; Bukalo, Olena; Silverstein, Shana; Holmes, Andrew; Kash, Thomas Louis
Abstract: Chronic stress contributes to the neuropathology of mental health disorders, including those associated with anxiety. The basolateral amygdala (BLA) coordinates emotional behavioral responses through glutamatergic outputs to downstream regions such as the prefrontal cortex (PFC), nucleus accumbens core (NAcc) and bed nucleus of the stria terminalis (BNST). We explored the effects of chronic stress on BLA outputs to the PFC, NAcc and BNST using slice electrophysiology combined with optogenetics in two inbred mouse strains with distinct stress-induced anxiety responses. We found that ten consecutive days of chronic restraint stress enhanced pre-synaptic glutamate release at BLA-to-PFC synapses in C57BL/6J mice, but reduced pre-synaptic glutamate release at these synapses in DBA/2J mice. To assess the behavioral relevance of enhanced glutamate output at BLA-to-PFC synapses, we approximated the effects of chronic stress on the BLA-PFC circuit using optogenetics. We found that photostimulation of the BLA-PFC circuit in unstressed C57BL/6J mice produced persistent (i.e., post-stimulation) increased anxiety-like behavior and hyperactivity in the elevated plus-maze - a profile consistent with prototypical behavioral responses of stressed C57BL/6J mice. These data demonstrate that chronic stress dysregulates the BLA-PFC circuit by altering pre-synaptic glutamate release from BLA outputs, and provide a mechanism by which chronic stress can lead to increased anxiety. Highlights: Chronic stress strain-dependently dysregulates glutamate release at BLA-to-PFC synapses. Chronic stress does not alter glutamate release at other BLA projection targets investigated. Post-synaptic glutamate transmission is not altered by chronic stress. Photostimulating the BLA-PFC circuit increases anxiety-like behavior in unstressed mice.